Meningkatkan Kemahiran Membaca Teks Bahasa Arab melalui Metode Kooperatif Mahasiswa STAI PUI Majalengka - Sya’adtul Kamilah, Dedeh (AlFaqrah: Journal of Arabic Studies, 2019)
This is a classroom action research which has a goal to know the effectiveness of cooperative learning to improve the students’ability in reading Arabic text of PESKAM students of STAIN Samarinda. The population of the study is 116 students from 4 Arabic laguage classes. The data were analyzed by using paired t-test. The result of the study shows that the Arabic text reading ability of the students before the implementation of cooperative learning is 72.3, meanwhile the Arabic text reading ability of the students before the implementation of cooperative learning is 86.53. It means that cooperative learning is effective to improve the Arabic text reading ability of the students. From the aspect of motivation, cooperative learning could improve their motivation to learn Arabic which could improve as 56.9%. From the findings of the study, it is concluded that cooperative learning significantly improved thestudents’ability in reading Arabic text of PESKAM students of STAIN Samarinda. It also improved the students’ motivation learn Arabic text.